2013
DOI: 10.1007/s11906-013-0386-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and the Prevention of Hypertension

Abstract: As the worldwide prevalence of hypertension continues to increase, the primary prevention of hypertension has become an important global public health initiative. Physical activity is commonly recommended as an important lifestyle modification that may aid in the prevention of hypertension. Recent epidemiologic evidence has demonstrated a consistent, temporal, and dose-dependent relationship between physical activity and the development of hypertension. Experimental evidence from interventional studies have fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
280
5
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(325 citation statements)
references
References 70 publications
18
280
5
22
Order By: Relevance
“…Most studies have shown that physical activity may reduce high levels of arterial blood pressure in hypertensive subjects [21]. However, in the present study this reduction did not found.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Most studies have shown that physical activity may reduce high levels of arterial blood pressure in hypertensive subjects [21]. However, in the present study this reduction did not found.…”
Section: Discussioncontrasting
confidence: 90%
“…Epidemiological studies have revealed an association between low level of physical activity and the presence of hypertension. Furthermore, randomized clinical trials and meta-analyzes have con irmed that regular exercise can reduce blood pressure levels, improve quality of life, and interfere positively in the cardiovascular risk factors [3].…”
Section: Introductionmentioning
confidence: 99%
“…The American College of Sports Medicine recommends dynamic aerobic endurance training for at least 30 min daily to prevent hypertension [31], and randomized control studies repeatedly show that exercise reduces SBP and DBP [32]. There seems to be strong evidence for an effect of physical activity interventions on blood pressure not only among hypertensive but also among normotensive and prehypertensive individuals [33]. However, in our study we found no association between change in leisure time physical activity and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) significantly reduces blood pressure (BP) in individuals with hypertension (high BP) and reduces the risk of incident hypertension in individuals with normal BP [1]. However, this influence has been shown to be modulated by genetic variants such that certain subpopulations do not experience the antihypertensive benefits of PA [2].…”
Section: Introductionmentioning
confidence: 99%